Books between Europe and the Americas
XII, 317 p.
Keywords: A ground-breaking collection by thirteen distinguished international scholars; this volume presents fresh perspectives on the exchange of culture and ideas between isolated communities through books and correspondence, and offers pioneering comparisons between the northern Atlantic and that of Spanish and Portuguese territories further south.